Efek Mediasi Kepuasan Kerja : Dampak Fasilitas, Work-Life Balance dan Disiplin Kerja Terhadap Kinerja Pegawai - Herman Sjahruddin; Buyamin Buyamin; Rabihatun Idris; Armin Saputra (Jurnal Ecogen, 2022)
This study aims to analyze the factors that affect employee satisfaction and performance. There are several articles that have explored the creation of satisfaction and performance in organizations. This study was conducted at the North Makassar II Samsat Office. Sampling uses total sampling, which draws the entire population of 65 respondents (employees). The research analysis technique uses structural equation modeling (SEM) with the help of partial least squares (PLS). The results of direct hypothesis testing show that work facilities have a significant effect on satisfaction and performance, work-life balance is significant on satisfaction but not significant on performance, for work discipline has no significant effect on satisfaction but has a significant effect on performance. Meanwhile, the indirect hypothesis shows that job satisfaction is significantly positive mediating the effect of work-life balance on performance. Job satisfaction cannot mediate the variables of work facilities and work discipline on employee performance.